2016
DOI: 10.4314/gjpas.v22i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cement dust pollution on respiratory systems of Lafarge cement workers, Ewekoro, Ogun State, Nigeria

Abstract: In this investigation, the impact of cement dust pollution on respiratory systems of Lafarge cement workers was evaluated. A total of 120 respondents; 60 from the factory workers and 60 (controls) from Ifo, a nearby village 22 km NE of the factory were interviewed in 2014 using a modified respiratory symptom score questionnaire. Two hypotheses were formulated in null form and tested at 95% probability level. Descriptive statistics, independent and dependent t-tests were used to compare treatments while Analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
1
8
1
Order By: Relevance
“…Hence, increase to exposure of high concentration of particulate matters from cement dust can adversely deteriorate factory workers' health. This data is in accordance with the findings by Chukwu and Ubosi (2016) and Nkhama (2017).…”
supporting
confidence: 94%
See 2 more Smart Citations
“…Hence, increase to exposure of high concentration of particulate matters from cement dust can adversely deteriorate factory workers' health. This data is in accordance with the findings by Chukwu and Ubosi (2016) and Nkhama (2017).…”
supporting
confidence: 94%
“…Critical examination of Figure 5 revealed that respondents who worked in the storage and transportation section of the factory had the highest percentage (77.3%) in the use of PPE against respondents from cement milling and blending section with the least percentage ratio of (54.5%). This finding disagreed with earlier submission by Chukwu and Ubosi (2016) H02: There is no significant relationship between the perceived health risk associated with cement dust exposure and factory workers' health Examination of data as displayed in Table 4 revealed a significant relationship between the perceived health risk associated with cement dust exposure and the health of factory workers at 0.05 level. This implies that a significant relationship exist between the perceived health risks associated with cement dust exposure and the health of factory workers.…”
contrasting
confidence: 88%
See 1 more Smart Citation
“…Various research has shown that at different stages of cement production, there is release of dust [23,29]. The nature and amount of the raw materials as well as the topography, and weather conditions affect the concentration of the dust and dispersal patterns.…”
Section: Pollutants Sources and Classificationmentioning
confidence: 99%
“…6 Lime is an alkaline material and corrodes biological tissues; silica is a skin abrasive and also damages the lungs; and chromium causes allergic reactions. 7 Many of the studies 3,4,6,8,9,10 done previously demonstrated the effect of cement dust on respiratory system. These studies found out considerable decline in the lung function parameters due to cement dust inhalation.…”
Section: 3mentioning
confidence: 99%